Comparison of the antifungal and antibacterial effect of the essential oil and ethanolic extract of the Zingiber officinale Rhizome (Ginger) cultivated in the San Carlos zone, Costa Rica in order to standardize a hydroponic medicinal cultivation of the same - González Guevara, Jean Carlo (2020)
Introduction: Ginger is a medicinal plant native to India. Its potential use in cosmetics, medicines and natural products has been reported, however depending on the conditions of cultivation the medicinal components of the different parts of the plant not only changes in its concentration, but in its composition, this modifies its action medicinal. Objective: Characterize the chemical composition of the essential oil obtained from the rhizomes of Zingiber officinale cultivated in the San Carlos area, Costa Rica, and to compare its antifungal and antibacterial effect in order to standardize future crops of the plant. Hydroponic form and validate its pharmacological effect and, or Cosmetic a posteriori. Materials and Methods: The rhizomes of the plant were used, the active ingredients were extracted by ethanolic extraction with Soxhlet and steam distillation, the analysis was performed by a qualitative phytochemical profile for the ethanolic extract, and the composition of the essential oil was studied by means of Gas Chromatography coupled to a mass detector (GC-MS). In addition, microbiological tests were performed by plate diffusion for ethanolic extracts and essential oil with strains of bacteria and fungi common in cutaneous pathologies. By means of a scanning electron microscope. Results and Conclusions: The presence of flavonoids, alkaloids, saponins, tannins and triterpenes in the ethanolic extract was qualitatively determined. In the characterization of the essential oil by GC-MS, geranial (27.42%), neral (20.11%), 1,8-cineol (13.35%), camphene (4.65%) and E-geraniol%). The composition obtained with the composition reported in the literature was compared, obtaining a clear difference with that reported in other studies, which allows to predict an antimicrobial behavior different from most of the traditional essential oils of this rhizome. It was determined that the essential oil inhibited the growth of Staphylococcus aureus, Escherichia coli, Streptococcus pyogenes, Stahylococcus epidermidis, Candida albicans, Enteroccocus faecalis, but not against Pseudomonas aureginosa, the ethanolic extract showed no antifungal or antibacterial activity, in addition it was demonstrated that the oil Essential has a stronger anti-Candida Albicans effect than inhibition halo at the same concentration of essential oil and that its mechanism of action included destruction of the membrane by pore formation and an osmotic shock.